Léopold Senghor e a Lusofonia : entre conceitos, diálogos e recepções (1957-1988) - Scholl, Camille Johann (2021)
This research explains how Léopold Sédar Senghor participates in debates about the idea of Lusophony, as a political concept in constant production of meanings, also argues that this Senegalese intellectual inscribes this concept in the political debate in the period from 1957 to 1988. Inspired by the theoretical-methodological approach of intellectual history and history of concepts, this work has two approaches, concerning the intentions for the construction of the Luso-Afro-Brazilian Community, looking at concepts (lusitanity, latinity, negritude, africanity e brasility) and dialogues (between Léopold Senghor, Carlos Lacerda, Amílcar Cabral, António de Spínola, Mário Gibson Barboza and Mário Soares). This approach demonstrates how different forms of reception of Senghor in different spaces of Lusophony (Portugal, Brazil and Guinea-Bissau) after the Carnation Revolution, contributing to think about layers of discourse about Lusophony.